2022
DOI: 10.3389/fsurg.2022.897550
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Critical Illness Score, Clinical Characteristics and Comprehensive Treatment of Children with Severe Mycoplasma Pneumoniae Pneumonia

Abstract: ObjectiveTo investigate the clinical characteristics of children with severe Mycoplasma pneumoniae pneumonia (SMPP) and the correlation with pediatric critical illness score (PICS), and to explore the effect of combined treatment with antibiotics and glucocorticoids.MethodsThe medical records of 120 children with SMPP admitted to our hospital from January 2020 to June 2021 were retrospectively analyzed. Children with a PICS score greater than 80 within 24 h of admission were included in the non-critical group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Clinically, glucocorticoid is commonly used for MPP treatment and the improvement of inflammatory response. 23 In this study, the clinical treatment of budesonide combined with N-acetylcysteine by aerosol inhalation was effective. Aerosol inhalation of therapeutic drugs can directly act on bronchial mucosa, promote continuous local precipitation of drugs, prolong antiinflammatory time, and avoid liver first-pass effect, which can help to improve airway inflammation quickly.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Clinically, glucocorticoid is commonly used for MPP treatment and the improvement of inflammatory response. 23 In this study, the clinical treatment of budesonide combined with N-acetylcysteine by aerosol inhalation was effective. Aerosol inhalation of therapeutic drugs can directly act on bronchial mucosa, promote continuous local precipitation of drugs, prolong antiinflammatory time, and avoid liver first-pass effect, which can help to improve airway inflammation quickly.…”
Section: Discussionmentioning
confidence: 75%
“…Clinically, glucocorticoid is commonly used for MPP treatment and the improvement of inflammatory response 23 . In this study, the clinical treatment of budesonide combined with N‐acetylcysteine by aerosol inhalation was effective.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…At present, glucocorticoid has been widely used in the treatment of RMPP and helps to control the progress of the disease and accelerate clinical recovery. [21][22][23] Those cases that need systemic glucocorticoid therapy tend to be more severe and refractory indicating that it is more likely to develop into delayed radiographic recovery. In addition, this study also found that extrapulmonary complications are a risk factor for delayed radiographic recovery.…”
Section: Discussionmentioning
confidence: 99%